Russia's youth and its culture : a nation's constructors and constructed - Pilkington, Hilary, 1964- (Routledge, 1994)
Applies the methods of cultural studies research to Russian youth, deconstructing social discourse and providing an alternative reading based on unique ethnographic fieldwork from Moscow.